(untitled) (Journal of Philosophy, Culture and Political Science, 2018)
This article is dedicated to the analysis of views to the culture of the kazakhs ethic, the spokesmen of the reformer liberal-democratic intelligentsia of the 20th century. It also considers the negative influence of the soviet totalitarism that caused a heavy blow to the culture of the ethic of the traditional kazakh society